1987
DOI: 10.1111/j.1528-1157.1987.tb03641.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolonged Anticonvulsant Medication in Epileptic Patients: Serum Lipids, Vitamins B6, B12, and Folic Acid, Proteins, and Fine Structure of Liver

Abstract: Twenty-seven epileptic patients, most from low socioeconomic groups and aged 15-54 years, were studied for effects of prolonged anticonvulsant medication. They had received the usual doses of phenobarbitone and diphenylhydantoin (PHT) regularly for 3-32 years, with control of seizures, and had not taken any B-vitamins in the year before investigation. Besides reduced serum and cerebrospinal fluid (CSF) folate levels, significantly increased levels of total vitamin B6 in CSF and serum and of vitamin B12 in seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 33 publications
2
11
1
1
Order By: Relevance
“…The significantly increased triglycerides values are detected mainly in the carbamazepine treated group (P < 0.05). This finding is in accordance with that of Datsur and Dave [26] . The possible mechanism of the increased level of triglycerides is the inhibition of β-oxidation of fatty acids due to carnitine deficiency and as a result, the fatty acids will be directed to triglyceride synthesis [27] .…”
Section: Discussionsupporting
confidence: 93%
“…The significantly increased triglycerides values are detected mainly in the carbamazepine treated group (P < 0.05). This finding is in accordance with that of Datsur and Dave [26] . The possible mechanism of the increased level of triglycerides is the inhibition of β-oxidation of fatty acids due to carnitine deficiency and as a result, the fatty acids will be directed to triglyceride synthesis [27] .…”
Section: Discussionsupporting
confidence: 93%
“…Being on phenytoin and phenobarbital was associated with statistically higher levels of total cholesterol (Dastur and Dave, 1987), while higher levels of HDL were found when phenytoin and phenobarbital were used together. (Luoma et al, 1982(Luoma et al, , 1980 On the other hand, being on carbamazepine and valproic acid was associated with significantly lower levels of HDL.…”
Section: Aed Polytherapy Vs Not On Aeds Comparison Group (S Table 2)mentioning
confidence: 89%
“…17 On the contrary, in a study showed that serum vitamin B12 concentration were elevated in all patients. 11 Increased circulating vitamin B12 level, however, served as a sensitive biochemical index of hepatic damage due to anticonvulsants 18 . Prolonged drug treatment was possibly the cause of the slightly impaired ability of the liver to store vitamin B12.…”
Section: Discussionmentioning
confidence: 99%